2021
DOI: 10.1111/jfpp.15937
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phenolics and antioxidant capacity during fermentation and simulated in vitro digestion of mango puree fermented with different lactic acid bacteria

Abstract: Mangoes (Mangifera indica L.) are popular seasonal fruit in Reunion Island and are regarded as a good source of dietary antioxidants, such as ascorbic acid, carotenoids, and mangiferin, and flavonoids (Ma et al., 2011). Mango pulps contains gallic acid, chlorogenic acid, vanillic acid and protocatechuic acid and gallic acid has been described as the predominant phenolic compound (Palafox-Carlos et al., 2012). The total phenolic content is higher than the total carotenoids in mango fruit (Fratianni et al., 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…plantarum, Lc., L. acidophilus Flavonoid glycosidase Cyanidin-3- O -glucoside, peonidin-3- O -glucoside/peonidin-3- O -galactcoside, quercetin-3- O -rhamnoside; Cyanidin, petunidin, quercetin, kaempferol; ( Kwaw et al, 2018 ; Tang et al, 2021 ) Mango and Papaya puree Lp. plantarum, W. cibaria Flavonoid glycosidase, tannase, chlorogenic acid esterase Gallocatechin gallate, chlorogenic acid; Quercetin, ellagic acid; ( Mashitoa et al, 2021a , 2021b ) Acerola cherry puree Lc. casei, L. acidophilus Flavonoid glycosidase, chlorogenic acid esterase Hesperidin, rutin, chlorogenic acid; Caffeic acid; ( de Assis et al, 2021 ) Avocado puree Lp.…”
Section: Transformation Of Phenolic Compounds In Food Fermentationsmentioning
confidence: 99%
“…plantarum, Lc., L. acidophilus Flavonoid glycosidase Cyanidin-3- O -glucoside, peonidin-3- O -glucoside/peonidin-3- O -galactcoside, quercetin-3- O -rhamnoside; Cyanidin, petunidin, quercetin, kaempferol; ( Kwaw et al, 2018 ; Tang et al, 2021 ) Mango and Papaya puree Lp. plantarum, W. cibaria Flavonoid glycosidase, tannase, chlorogenic acid esterase Gallocatechin gallate, chlorogenic acid; Quercetin, ellagic acid; ( Mashitoa et al, 2021a , 2021b ) Acerola cherry puree Lc. casei, L. acidophilus Flavonoid glycosidase, chlorogenic acid esterase Hesperidin, rutin, chlorogenic acid; Caffeic acid; ( de Assis et al, 2021 ) Avocado puree Lp.…”
Section: Transformation Of Phenolic Compounds In Food Fermentationsmentioning
confidence: 99%
“…“Cogshall”) purée was more inhibitory than the not‐fermented one. [ 43 ] The polyphenol composition of pineapple, different from that of papaya and mango, probably explained a more limited effect on α‐glucosidase inhibition of lactic fermented pineapple. [ 44 ] Probiotics can enhance fasting and postprandial blood glucose, glucose tolerance, and hepatic glycogen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, these organic acids produced during proteolytic fermentation have been demonstrated for antiinflammatory properties, antibacterial, immune potentiating, anti-obesity, inflammation regulation, and growth promoters. Mashitoa et al (2023) study reported that the organic acid present in sweet potato smoothies fermented by L. plantarum includes tartaric acid, malic, gluconic, ribonic, isocitric, lactic, and acetic acids, which contribute to flavour and taste attributes of the fermented smoothies. Kanjan & Sakpetch (2023) found that the organic acid in cell-free supernatants of L. plantarum 124, which are lactic acid (49.57%) and acetic acid (25.85%), could extend the shelf life of Thai curry (Kaeng-Tai-Pla-Haeng) from 7 days to 21 days without any commercial preservatives.…”
Section: Organic Acidmentioning
confidence: 99%